Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0736-5748(99)00096-9
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity in neurological disorders — the glutamate paradox

Abstract: Beneficial effects of glutamate-receptor antagonists in models of neurological disorders are often used to support the notion that endogenous excitotoxicity (i.e. resulting from extracellular accumulation of endogenous glutamate) is a major contributor to neuronal death associated with these conditions. However, this interpretation conflicts with a number of robust and important experimental evidence. Here, emphasis is placed on two key elements: (i) very high extracellular levels of glutamate must be reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 57 publications
2
73
0
1
Order By: Relevance
“…stroke and anoxia). Obrenovitch et al (2000) suggested that glutamate neurotoxicity is a multifactorial process and glutamate neurotoxicity is not directly related to glutamatergic transmission but to inadequate energy supply (i.e. a mitochondrial dysfunction).…”
Section: Summary Discussion Implications and Outlookmentioning
confidence: 99%
“…stroke and anoxia). Obrenovitch et al (2000) suggested that glutamate neurotoxicity is a multifactorial process and glutamate neurotoxicity is not directly related to glutamatergic transmission but to inadequate energy supply (i.e. a mitochondrial dysfunction).…”
Section: Summary Discussion Implications and Outlookmentioning
confidence: 99%
“…However, neuronal over-stimulation by glutamate is responsible for both acute (McEwen and Magarinos, 1997;Akins and Atkinson, 2002) and chronic (Coyle and Puttfarcken, 1993;Doble, 1999;Hertz et al, 1999;Obrenovitch et al, 2000;Atlante et al, 2001;Pitt et al, 2003) neurodegenerative conditions. Excitotoxicity results from over-exposure of neurons to high concentrations of glutamate as a result of increased synthesis activity, decreased levels of catabolism, decreased transporter activity, and delayed re-uptake from the synaptic cleft after its release into the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy that MEAs detect neuronally derived glutamate, whereas microdialysis samples extracellular glutamate derived from non-neuronal origins, may be because of the inherent differences in the methodologies. The extensive damage to the local brain area during implantation of the microdialysis probe and the large area of tissue sampled (1-4 mm in length), restricts microdialysis measurements of glutamate to large regions far beyond synapses (Borland et al, 2005;Hillered et al, 2005;Jaquins-Gerstl and Michael, 2009;Obrenovitch, 1999, Obrenovitch et al, 2000Timmerman and Westerink 1997). Furthermore, the inadequate temporal resolution of microdialysis (*1-20 min) prevents microdialysis from detecting the rapid dynamic changes in extracellular glutamate that occur in the order of milliseconds to seconds (Diamond, 2005).…”
Section: Calcium Channel Dependent Neuronal Glutamate Release Contribmentioning
confidence: 99%